Pengaruh Kualitas Kehidupan Kerja Perawat Terhadap Kinerja Perawat di Rumah Sakit Dr. Pirngadi Medan: Pengaruh Kualitas Kehidupan Kerja Perawat Terhadap Kinerja Perawat - Siti Mariani Damanik; Arlina Nurbaity Lubis; Etti Sudaryati; Siti Saidah Nasution (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2022)
The quality of work-life has an impact on workers, one of which is the performance of these workers will increase. This can be a positive impact on workers and companies. The study was to analyze the effect of the quality of nurses' work life on the performance of nurses at Dr. Hospital. Pirngadi Medan. The study was non-experimental quantitative research with a cross-sectional descriptive approach. Seventy-four nurses were selected using random sampling. The results of the study on the quality of nurse's work-life(QNWL) were the majority in the sufficient category (score 91-135) as many as 42 people (56.8%), nurses' performance the majority of nurses had sufficient performance (score 71-110) as many as 47 people (63.6%). The quality of nurses’ work-life(QNWL) on nurse performance has a significance value of 0.004 <0.005. Suggestions for education as an additional reference in the development of nursing education regarding the quality of nurses' work life, for nursing services as an input for nursing in carrying out nursing care to patients as nurse performance, for future researchers as a reference for comparison for research. The next step is about the Quality of Nurses' Work-Life (QNWL) with different variables.